2016
DOI: 10.5194/hess-20-2841-2016
|View full text |Cite
|
Sign up to set email alerts
|

Model-based study of the role of rainfall and land use–land cover in the changes in the occurrence and intensity of Niger red floods in Niamey between 1953 and 2012

Abstract: Abstract. Since 1950, the Niger River basin has gone through three main climatic periods: a wet period (1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960), an extended drought (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980) and since 1990 a recent partial recovery of annual rainfall. Hydrological changes co-occur with these rainfall fluctuations. In most of the basin, the rainfall deficit caused an enhanced discharge deficit, but in the Sahelian region the runoff increased des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…If this variable is only taken into account (simulation "P"), simulated surface runoff decreases rather than increasing over time. This is in line with Descroix et al (2013), Casse et al (2016) and Aich et al (2015), who found that the modest increase in large rainfall amount (events > 40 mm) observed during the 2000s cannot alone explain the Sahelian paradox. However, this should be taken with caution because changes in precipitation not statistically detectable here may have occurred elsewhere, due to the high natural variability, and further studies are required to address this question in more detail.…”
Section: Attribution Of the Sahelian Paradoxsupporting
confidence: 87%
“…If this variable is only taken into account (simulation "P"), simulated surface runoff decreases rather than increasing over time. This is in line with Descroix et al (2013), Casse et al (2016) and Aich et al (2015), who found that the modest increase in large rainfall amount (events > 40 mm) observed during the 2000s cannot alone explain the Sahelian paradox. However, this should be taken with caution because changes in precipitation not statistically detectable here may have occurred elsewhere, due to the high natural variability, and further studies are required to address this question in more detail.…”
Section: Attribution Of the Sahelian Paradoxsupporting
confidence: 87%
“…In the same MNRB, Cassé et al [54] observed that the Upper Niger contribution has followed the climatic trend, and inversely, that "the local runoff contribution has been continuously increasing over the 1953-2012 period, which is paradoxical given the rainfall signal" ( [54], p. 2853). The opposite evolution between upstream and downstream signals results in the progressive increase of the "red" flood since the 1980s.…”
Section: A Marked Increase In Runoff Coefficients and Discharges Of Smentioning
confidence: 99%
“…Aich et al [93] and Cassé et al [54] showed that during the dry period (1st Sahelian paradox), LULCC was the main explanatory factor of the increasing stream flows, while, since the annual rainfall recovery period (since the end of the 20th century), rainfall intensification has also contributed to this trend, the respective roles of both being difficult to determine. In addition, two series of facts could complete this statement:…”
Section: Main Trends Described In Recent Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, a regional committee was set up to provide seasonal drought outlooks, informed by various monitoring and forecasting systems (e.g., Sheffield et al, 2014). Since then, land cover changes and wetter conditions has increased runoff coefficients and river discharge, particularly in the Sahelian zone (Aich et al, 2015;Amogu et al, 2010;Casse, Gosset, Vischel, Quantin, & Tanimoun, 2016). This has resulted in higher flood peaks, arriving earlier in the season (Mahé & Paturel, 2009).…”
mentioning
confidence: 99%